INTEGRATION OF ARTIFICIAL INTELLIGENCE AND AUGMENTED REALITY IN LEARNING IN THE 5.0 ERA - Loso Judijanto; Agry Alfiah; Wakhibah Dwi Khusnah (FAKULTAS TARBIYAH INSTITUT AGAMA ISLAM SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2025)
Era 5.0 brings significant changes in several aspects of life, including the education sector. The use of Artificial Intelligence (AI) and Augmented Reality (AR) has created new ways to make learning experiences more interactive, adaptive, and personalized. This study aims to examine the integration of AI and AR in learning, exploring the benefits, challenges, and implications of the technology at various levels of education. AI enables the development of intelligent learning systems that can adjust materials according to individual needs, while AR provides interactive visualizations and simulations that enrich the learning process. The results of the study show that the integration of these two technologies can increase student engagement, learning effectiveness, and understanding of complex concepts. However, challenges such as implementation costs, infrastructure readiness, and teacher training remain major obstacles. Therefore, collaboration is needed between educational institutions, the government, and the technology sector to ensure optimal use of AI and AR in supporting education in the 5.0 era.